A High Throughput Platform to Minimize Voltage and Fill Factor Losses - Haffner-Schirmer, Julian; Le Corre, Vincent Marc; Forberich, Karen; Egelhaaf, Hans-Joachim; Osterrieder, Tobias; Wortmann, Jonas; Liu, Chao; Weitz, Paul; Heumüller, Thomas; Bornschlegl, Andreas; Wachsmuth, Josua; Distler, Andreas; et al. (Advanced Energy Materials, 2025)
Organic photovoltaics (OPV) now can exceed 20% power conversion efficiency in single junction solar cells. To close the remaining gap to competing technologies, both fill factor and open-circuit voltage must be optimized. The Langevin reduction factor is a well-known concept that measures the degree to which charge extraction is favored over charge recombination. It is therefore ideally suited as an optimization target in high-throughput workflows; however, its evaluation so far requires expert interaction. Here, an integrated high-throughput workflow is presented, able to obtain the Langevin reduction factor within a few seconds with high accuracy without human intervention and thus suited for autonomous experiments. This is achieved by combining evidence from UV–vis spectra, current–voltage curves, and a novel implementation of microsecond transient absorption kinetics allowing, for the first time, the intrinsic determination of charge absorption cross-sections, which is crucial to reporting stationary charge densities. The method is demonstrated by varying the donor:acceptor ratio of the high performance OPV blend PM6:Y12. The high reproducibility of the method allows to find a strictly exponential relationship between the PM6 exciton energy and the Langevin reduction factor.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge dynamics; high throughput; Langevin reduction factor; organic photovoltaics; transient absorption kinetics

An Automated Workflow to Discover the Structure-Stability Relations for Radiation Hard Molecular Semiconductors - Bornschlegl, Andreas; Duchstein, Patrick; Wu, Jianchang; Rocha-Ortiz, Juan S.; Caicedo-Reina, Mauricio; Ortiz, Alejandro; Insuasty, Braulio; Zahn, Dirk; Lüer, Larry; Brabec, Christoph (Journal of the American Chemical Society, 2025)
Emerging photovoltaics for outer space applications are one of the many examples where radiation hard molecular semiconductors are essential. However, due to a lack of general design principles, their resilience against extra-terrestrial high-energy radiation can currently not be predicted. In this work, the discovery of radiation hard materials is accelerated by combining the strengths of high-throughput, lab automation and machine learning. This way, a large material library of more than 130 organic hole transport materials is automatically processed, degraded, and measured. The materials are degraded under ultraviolet-C (UVC) light in a nitrogen atmosphere, serving as the conditions for electromagnetic radiation hardness tests. A value closely related to the differential quantum yield for photodegradation is extracted from the evolution of the UV-visible (UV-vis) spectra over time and used as a stability target. Following this procedure, a stability ranking spanning over 3 orders of magnitude was obtained. Combining Gaussian Process Regression based on predictors from structural fingerprints and manual filtering of the materials by features, structure-stability relations for UVC stable materials could be found: Fused aromatic ring clusters are beneficial, whereas thiophene, methoxy and vinylene groups are detrimental. Comparing the UV-vis spectra of the degraded material in film and solution, bond cleavage could be made out as the leading degradation mechanism. Even though UVC light can in principle break most organic bonds, the stable materials are able to distribute and dissipate the energy well enough so that the chemical structures remain stable. The established predictive model quantifies the effect of specific molecular features on UVC stability, allowing chemists to consider UVC stability in their molecular design strategy. In the future, a larger data set will allow to inversely design molecular semiconductors which show high performance and radiation hardness at the same time.
CRIS-Team Scopus Importer:2025-01-31

Enhancing Planar Inverted Perovskite Solar Cells with Innovative Dumbbell-Shaped HTMs: A Study of Hexabenzocoronene and Pyrene-BODIPY-Triarylamine Derivatives - Rocha-Ortiz, Juan S.; Wu, Jianchang; Wenzel, Jonas; Bornschlegl, Andreas; Perea, Jose Dario; Leon, Salvador; Barabash, Anastasia; Wollny, Anna-Sophie; Guldi, Dirk Michael; Zhang, Jiyun; Insuasty, Alberto; Lüer, Larry; et al. (Advanced Functional Materials, 2023)
Keywords: hexabenzocoronene; donor–acceptor; BODIPY; π-conjugation; perovskite solar cells; hole-transport materials

Tailoring the Dimensionality of 2D/3D Heterojunctions for Inverted Perovskite Solar Cells - Li, Chaohui; Zhang, Kaicheng; Maiti, Santanu; Peng, Zijian; Tian, Jingjing; Park, Hyoungwon; Byun, Jiwon; Xie, Zhiqiang; Dong, Lirong; Qiu, Shudi; Bornschlegl, Andreas; Liu, Chao; et al. (ACS Energy Letters, 2024)
Interface engineering is crucial to achieving stable perovskite photovoltaic devices. A versatile approach is developed to tailor interface properties via integrating co-assembled monolayers (co-SAMs) at the p-type buried interface and by capping a two-dimensional (2D) perovskite layer at the n-type upper interface with vacuum quenching. Optimized co-SAMs promote the coverage of the hole transport layer, significantly reducing the incidence of leakage currents. Based on this foundation, we develop damp-heat-stable perovskite solar cells by precisely tailoring the fragments of 2D perovskite layers through vacuum annealing with phenethylammonium iodide. An impressive open-circuit voltage of 1.216 V is achieved, corresponding to 92% of the value determined by the detailed-balance limit, along with a power conversion efficiency of 23.68%. Ultimately, integrating co-SAMs and the vacuum-assisted annealing fabricated devices maintain 96% and 80% of initial efficiencies after 1200 and 500 h of tracking at a maximum power point under 55 and 85 °C, respectively.
CRIS-Team Scopus Importer:2024-02-23

Unveiling the Role of BODIPY Dyes as Small-Molecule Hole Transport Material in Inverted Planar Perovskite Solar Cells - Seoneray, Isabel; Wu, Jianchang; Rocha-Ortiz, Juan S.; Bornschlegl, Andreas; Barabash, Anastasia; Wang, Yunuo; Lüer, Larry; Hauch, Jens; García, Angélica; Zapata-Rivera, Jhon; Brabec, Christoph J.; Ortiz, Alejandro (Solar RRL, 2024)
Perovskite solar cells (PSCs) have become a research hotspot since their dramatic increase in power conversion efficiency (PCE), surpassing 26% due to advances in cell engineering and interfacial layers. Within the last factor, hole transporting materials play a crucial role in enhancing device performance and stability. Among several molecular building blocks, BODIPYs are attractive for the design of novel hole transporting material (HTMs) due to their outstanding photophysical and charge transport properties easily tuned by synthetic modifications. Herein, the synthesis of five new BODIPY-based HTMs PyBDP 1–5 are reported, functionalized at the meso- and α- positions with pyrenyl and arylamino units, respectively. The resulting compounds exhibit broad absorption in the visible region, remarkable thermal stability, narrow bandgaps, suitable energy levels, and good hole extraction capability, as subtracted from experimental and computational characterizations. The performance of the BODIPY derivatives as HTMs is evaluated in planar inverted (p-i-n) PSCs and compared to commonly used PTAA, resulting in highly efficient systems, reaching PCEs very close to that obtained with the reference polymer (21.51%). The incorporation of these BODIPY-based HTMs result in an outstanding PCE of 20.37% for devices including PyBDP-1 and 19.97% for devises containing PyBDP-3, thus demonstrating that BODIPY derivatives are a promising alternative to obtain simple and efficient organic HTMs.
CRIS-Team Scopus Importer:2024-05-31
Keywords: arylamine; BODIPY; hole-transporting material; perovskite solar cells; pyrene